Using widely available geospatial data sets to assess the influence of roads and buffers on habitat core areas and connectivity - Jantz, P.; Goetz, S. (Natural Areas Journal, 2008)
Land development pressures that threaten habitat core areas and connectivity are intensifying across the nation and extending beyond urbanized areas in the form of rural residential development. This is particularly true in the temperate forests of the northeastern United States. We used a suite of nationally available data sets derived from satellite imagery to identify core habitat areas of the northeastern United States, including impervious cover (urbanized and developed areas) and forest cover (canopy density). These were augmented with road network extent and density. We analyzed the influence of different types of unimproved roads and amount of forest cover on identification of the extent and configuration of roadless areas, and then assessed these core habitat areas in terms of land ownership (public, private) and management (parks, refuges, multi-use). We also derived patch connectivity metrics using a graph theory approach, making use of cost surfaces that accounted for the above variables and associated landscape metrics. A case study linking suitable habitat for a keystone predator is explored. Because increased conversion and fragmentation of many roadless areas by exurban development will exacerbate the likelihood of local species extinctions, and complicate efforts to preserve intact functional ecosystems, our results suggest a starting point for the construction of a more comprehensive and ecologically functional reserve network for the region. The use of widely available data sets demonstrated the capability for similar analyses to be conducted nationally or for other regions.
Keywords: road density buffers core habitat connectivity graph theory cost surface